Remediation of Pb(II) and Cd(II) in Sea Water by Skeletonema costatum - Soedarti, Thin; Surtiningsih, Tini; Hariyanto, Sucipto; Kuncoro, Eko P. (Sustinere: Journal of Environment and Sustainability, 2017)
The heavy metals that polluted sea water can end up polluting fish pond too. Hence, it is necessary to remove the heavy metals before sea water enters the fish pond. The aim of this study was to know the growth, remediation ability, and the highest of removal efficiency of marine diatom Skeletonema costatum in the lead (Pb(II)) and cadmium (Cd(II)) solution. This study used 3 x 4 factorial design, i.e. concentrations of the cell inoculation (5000 cells mL-1; 10000 cells mL-1; and 15000 cells mL-1) and concentrations of Pb(II) and Cd(II) (0; 0.5; 1; and 2 ppm), replicated five times. During five day exposure time, the cell density was observed daily using a microscope (400X), while filtrate of media was analyzed using AAS. The result showed that S. costatum could grow in Pb(II) and Cd(II) at 2 ppm, and could remediate Pb(II) and Cd(II) at 2 ppm. The highest removal efficiency of marine diatom S. costatum in Pb(II) solution was 80.5% (5000 cells mL-1 at 2 ppm on the first day), and in Cd(II) solution was 80% (15000 cells mL-1 at 0.5 ppm on the fifth day).